2022
DOI: 10.7759/cureus.27538
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myeloid Leukemia Masquerading as Decompensated Cirrhosis

Abstract: Patients with known cirrhosis who present with anemia, thrombocytopenia, acute renal failure, and confusion are usually presenting with decompensated cirrhosis. We present a patient with known alcoholic cirrhosis presenting with the above abnormalities, initially thought to be decompensated cirrhosis but found to have acute myeloid leukemia (AML) with acute blast crisis. This case was presented as a poster at the American College of Gastroenterology Annual Scientific Meeting held on October 22-27, 2021.A 59-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…In retrospective studies, an overall survival benefit has only been observed in MS patients who underwent HSCT. Radiation is generally used in consolidation after induction chemotherapy, for treating localized recurrences after HSCT, and in palliative settings to reduce large tumor masses to relieve compression symptoms and reduce pain [15][16].…”
Section: Discussionmentioning
confidence: 99%
“…In retrospective studies, an overall survival benefit has only been observed in MS patients who underwent HSCT. Radiation is generally used in consolidation after induction chemotherapy, for treating localized recurrences after HSCT, and in palliative settings to reduce large tumor masses to relieve compression symptoms and reduce pain [15][16].…”
Section: Discussionmentioning
confidence: 99%
“…All cases reported are in adults and had presentations which were suggestive of malignancy in addition to raised liver enzymes/hyperbilirubinemia, and in pediatric almost 3 case reports with similar fashion. Recent case report in Arrowhead Regional Medical Center, Colton, USA, in 2023 reported a young adult, 18 years of age who presented with jaundice and transaminases with axillary LAD, family history positive for leukemia, with blasts cell evident in blood smear [1][2][3][4][5][6][7][8]. A 7 years old boy, reported as a case of ALL who also presented with history of transaminases which got worse over weeks, and was diagnosed with flow cytometry.…”
Section: Discussionmentioning
confidence: 99%